Regioselective Synthesis of α-Phosphinoylnaphthols through Rhodium-Catalyzed Annulation of 1-Alkynylphosphine Oxides with Sulfoxonium Ylides - Xie, Wucheng; Lin, Binting; Jian, Xinyi; Lin, Qinhong; Shi, Junjun (Synlett, 2020)
α-Phosphinoylnaphthols were obtained by redox-neutral annulation of 1-alkynylphosphine oxides with α-carbonyl sulfoxonium ylides under rhodium(III) catalysis. This protocol shows good regioselectivity and broad functional-group tolerance.
Keywords: C–H activation; rhodium catalysis; cyclization; carbocycles; phosphinoylnaphthols; ylides